2016
DOI: 10.4317/jced.53100
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of Wnt/β-catenin signaling pathway proteins in ameloblastoma and calcifying cystic odontogenic tumor

Abstract: BackgroundWnt/β-catenin signaling pathway is essential for the beginning of odontogenesis and may be involved in the development and progression of some odontogenic tumors. Thus, the aim of this study was to comparatively evaluate the immunohistochemical expression of Wnt/β-catenin signaling pathway proteins in a series of AME and CCOT.Material and MethodsImmunohistochemical reactions were performed using antibodies against Wnt1, Wnt5a and β-catenin in 17 cases of solid AME and 6 cases of CCOT.ResultsIn the AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Interestingly, COC ghost cells express WNT1 and WNT5A ligands, as well as Beta-catenin [116,117]. In immature odontomas, ghost cells showed weak Beta-catenin immunostaining, while adjacent epithelial cells exhibited a strong pattern in the nucleus and cytoplasm.…”
Section: The Wnt Pathway and Calcifying Odontogenic Cystmentioning
confidence: 99%
“…Interestingly, COC ghost cells express WNT1 and WNT5A ligands, as well as Beta-catenin [116,117]. In immature odontomas, ghost cells showed weak Beta-catenin immunostaining, while adjacent epithelial cells exhibited a strong pattern in the nucleus and cytoplasm.…”
Section: The Wnt Pathway and Calcifying Odontogenic Cystmentioning
confidence: 99%
“…Genetic alterations affecting abnormal activation of the Wnt pathway have been associated with the pathogenesis of cysts odontogenic tumors in particular BOGCL [12] [18] [19] [20] [21].It has been reported that the only genetic alteration found in COC is in the beta-catenin, which reinforces the suspicion that this mutation determines an alteration of the Wnt signaling pathway and this would be at the basis of tumorigenesis in COC[22] [23]. Hence, an altered signaling in the odontogenic epithelium coordinated by beta-catenin plays a role in pathogenesis of BOGCL[23] [24][25].Beta-catenin mutations with GC formation have been found in ameloblastoma cells confirming a relationship between these two cellular types[26]. It is plausible to think that an abnormal stimulus on cellular remains of the primitive lamina of the Serres determines the development of ameloblastoid cells that have a genetic alteration of the WNT pathway with abnormal beta-catenin activity, which in turn leads to the development of a more differentiated and less aggressive tumor of the ameloblastoma.…”
mentioning
confidence: 65%
“…The data pool contained 56 articles after removal of the duplicates. These were further screened to 34 after scrutinising the title and abstract and eligibility evaluation was assessed by full text reading 1–11,13–35 . The final selection included 34 articles for qualitative analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway is one of the prime regulators in the pathogenesis of odontogenic lesions, the activation of which stabilises beta catenin, facilitating its cytoplasmic accumulation and nuclear translocation. Within the nucleus it further participates in the expression of genes related to the cell cycle forming several complexes with DNA‐binding proteins such as TCF (T‐cell factor) and LEF‐1 (lymphoid enhancer factor‐1) which is involved in cell proliferation, inhibition of apoptosis, and invasion and migration of the tumour cells 4,5,7 . The inherent activation of beta catenin mediated transcription resultant from mutations in genes like adenomatous polyposis coli (APC) is suggested as a requisite in tumorigenesis in various types of benign and malignant lesions 8 .…”
Section: Introductionmentioning
confidence: 99%